Effects of whole body vibration on motor unit recruitment and threshold - Pollock, R. D.; Woledge, R. C.; Martin, F. C.; Newham, D. J. (Journal of Applied Physiology, 2012)
Whole body vibration (WBV) has been suggested to elicit reflex muscle contractions but this has never been verified. We recorded from 32 single motor units (MU) in the vastus lateralis of 7 healthy subjects (34 ± 15.4 yr) during five 1-min bouts of WBV (30 Hz, 3 mm peak to peak), and the vibration waveform was also recorded. Recruitment thresholds were recorded from 38 MUs before and after WBV. The phase angle distribution of all MUs during WBV was nonuniform (P < 0.001) and displayed a prominent peak phase angle of firing. There was a strong linear relationship (r = -0.68, P < 0.001) between the change in recruitment threshold after WBV and average recruitment threshold; the lowest threshold MUs increased recruitment threshold (P = 0.008) while reductions were observed in the higher threshold units (P = 0.031). We investigated one possible cause of changed thresholds. Presynaptic inhibition in the soleus was measured in 8 healthy subjects (29 ± 4.6 yr). A total of 30 H-reflexes (stimulation intensity 30% Mmax) were recorded before and after WBV: 15 conditioned by prior stimulation (60 ms) of the antagonist and 15 unconditioned. There were no significant changes in the relationship between the conditioned and unconditioned responses. The consistent phase angle at which each MU fired during WBV indicates the presence of reflex muscle activity similar to the tonic vibration reflex. The varying response in high- and low-threshold MUs may be due to the different contributions of the mono- and polysynaptic pathways but not presynaptic inhibition.